Aid for Refugees: Religion, Migration, and Poor Relief in Sixteenth-Century Geneva. Issue 1 (2nd January 2018) - Chung-Kim, Esther
ABSTRACT: During the sixteenth century, migration of mainly French Protestants into Geneva resulted in a significant refugee community dedicated to discipline and poor relief. This article examines the ongoing impact of migration on the formation of religious communities and their correlation with the development of poor relief funds in a leading Reformation city. The social dislocation of religious refugees fostered a high commitment to their new identity as advocates of the Reformed religion and proponents of poor relief for foreigners. John Calvin, chief minister and French immigrant, articulated his ideals for establishing a truly Christianized community through the institutions of the church, the consistory and the Bourse française (French Fund) to support the formation of a distinctive religious identity. This article argues that aid for the refugees became an integral part of establishing this religious and social reformation from the 1540s to the 1560s as waves of refugees landed in Geneva.